The current situation of children's nursing training in South Africa - Chukwu, Uchenna Nneka (Department of Public Health and Family Medicine, 2017)
The high rate of Infant and child mortality, much of which is preventable, especially in developing countries, continues to be a global public health concern. Improving the numbers and competencies of child nurse professionals is vital for health system strengthening. Child nurses are important group of health professionals who are responsible for delivering effective health care services to infants and children at all levels of the health system, yet their training situation is being under-investigated. It is documented in various literatures that the high rate of under-five morbidity and mortality in South Africa can be prevented by strengthening the training needs of child nurses, in order to ensure that their competencies adequately align with the priority health needs of children who present at the health facilities. This dissertation is organized into three parts. Part A is the research protocol which outlines the background and the study methodology. Mixed methods comprising qualitative and quantitative methods is adopted for the study. Documentary review and self-administered structured questionnaire is used for the data collection. The questionnaire is designed by applying the basic principles that informs a good questionnaire design. Purposive sampling method is used for sampling the nursing institutions and research participants for inclusion into the study. Defined inclusion and exclusion criteria are used to identify and select the Nursing Education Institutions and key informants suitable for the study. The nursing institutions that are accredited with the South African Nursing Council and conducts child health nursing is an inclusion criterion for the study. In addition, key informants who are nursing educators with expertise knowledge in children's nursing are identified as an inclusion criterion for the study. Documentary review is used to extract secondary data that identifies the South African policy and legislative framework for general nursing and children nursing in particular. Documents will include appropriate policy and strategy documents. The workshop minutes of a sentinel Nurse Educator Forum that took place at Groote Schuur hospital in December of 2016 will be included as an important secondary data source. In addition, primary data collection will be done using a self-administered structured questionnaire where key informants will address a combination of qualitative and quantitative questions. The self-administered questionnaire is used to thoroughly investigate the current situation of children's nursing training in South Africa, with the aim of identifying the numbers trained annually for a five-year period and the curriculum foci of children nursing training across the nursing institutions that host children nursing programs in South Africa. Part B is the literature review which examines the preventable causes of under-five mortality in South Africa and the need to train up suitable, well qualified and competent Child Nurse Professionals needed to improve the health of infants and children in South Africa. Part C is the journal article manuscript which begins with the background and the study methods, followed by the results, discussion and conclusion. The result indicates that a total of five relevant policy and strategy documents were identified for the documentary review. Of the five documents, three documents suggest strategies for improving the nursing education and training programmes in South Africa. The strategies include increasing the supply of the nurse specialists, transforming all nursing colleges to Higher Education Institutions and improving the curriculum guidelines of the nursing programme, in order to ensure that the competencies taught to the nurses aligns with the health care needs of the communities. The two other documents posit the primary roles of the nursing professionals, which is to provide effective care and respect the rights of the health care users. The findings from the documentary review recommends that the nursing education in SA can be strengthened by identifying all nursing colleges as Higher Education Institutions, reviewing curricula and producing more numbers of competent nurses in South Africa. For the primary data collection, out of the seven accredited nursing institutions which conducts children nursing training in South Africa, five respondents from five institutions completed and forwarded their questionnaires. The completed questionnaires provided details on the profile of children's nursing training, including the annual numbers of children nurse trainees and graduates over a five-year period and details of their curriculum components. The results showed that a total of 637 children nurses were enrolled from 2012-2016. Of the 637, 587 graduated successfully which indicates that the number of child nurse trainees and those who successfully graduated over a five -year period across five nursing institutions were very impressive, although the number of child nurses produced annually are still few to address the child health needs in South Africa. In addition, the findings from the questionnaire reveals that the curriculum of children's nursing training across the five institutions are similar and contains topics that are capable of equipping the child nurses with the relevant skills necessary for improving the health of infants and children. However, they exist some variations in the degree the courses are covered by the institutions, as well as variations in the way the courses are conveyed to the nurse learners. For example, some topics where covered to a high degree by some institutions, while some where not covered at all, or where covered to some extent via classroom and clinical placement and assessments. This suggests that the curricula of child nursing in South Africa requires standardization and frequent reviewing to ensure it coincides with the child health needs in South Africa. The dissertation is likely to increase the knowledge of the current training situation of children's nursing in South Africa, and also identify gaps for future research. In addition, the dissertation also provides a better understanding of the curriculum foci of children's nursing training in South Africa and can help inform the human resource training plans for child health nursing in the country.